Environmental ethics and jurisdiction relationships and interdependence - Misra, R.P. (1995)
"Establishing inseparable interdependence for survival of both Man and Nature and serious distortions brought about through former's deliberate acts in this relationship, the author emphasises the need of ethics (he identifies three approaches in this regard) in our actions having a bearing on environment. After looking at major causes of Man-Nature conflict he discusses limitations in efficacy of available legal remedies, and the rectify these, he suggests reinforcing mutually supplementing roles for law and ethics and linking inseparably environmental ethics with education for durable positive results"
Keywords: Environment - India; Ethics - India; Environment